Daily Preventive Zinc Supplementation Decreases Lymphocyte and Eosinophil Concentrations in Rural Laotian Children from Communities with a High Prevalence of Zinc Deficiency: Results of a Randomized Controlled Trial. Issue 8 (2nd March 2020) - Kewcharoenwong, Chidchamai; Schuster, Gertrud U; Wessells, K Ryan; Hinnouho, Guy-Marino; Barffour, Maxwell A; Kounnavong, Sengchanh; Brown, Kenneth H; Hess, Sonja Y; Samer, Waraporn; Tussakhon, Inthira; Peerson, Janet M; Lertmemongkolchai, Ganjana; et al.
ABSTRACT: Background: Zinc deficiency impairs immune function and is common among children in South-East Asia. Objectives: The effect of zinc supplementation on immune function in young Laotian children was investigated. Methods: Children ( n = 512) aged 6–23 mo received daily preventive zinc tablets (PZ; 7 mg Zn/d), daily multiple micronutrient powder (MNP; 10 mg Zn/d, 6 mg Fe/d, plus 13 other micronutrients), therapeutic dispersible zinc tablets only in association with diarrhea episodes (TZ; 20 mg Zn/d for 10 d after an episode), or daily placebo powder (control). These interventions continued for 9 mo. Cytokine production from whole blood cultures, the concentrations of T-cell populations, and a complete blood count with differential leukocyte count were measured at baseline and endline. Endline means were compared via ANCOVA, controlling for the baseline value of the outcome, child age and sex, district, month of enrollment, and baseline zinc status (below, or above or equal to, the median plasma zinc concentration). Results: T-cell cytokines (IL-2, IFN-γ, IL-13, IL-17), LPS-stimulated cytokines (IL-1β, IL-6, TNF-α, and IL-10), and T-cell concentrations at endline did not differ between intervention groups, nor was there an interaction with baseline zinc status. However, mean ± SE endline lymphocyte concentrations were significantly lower in the PZ than in the control group (5018 ± 158 compared with 5640 ± 160 cells/μL, P = 0.032). Interactions with baseline zinc status were seen for eosinophils ( P ixn = 0.0036), basophils ( P ixn = 0.023), and monocytes ( P = 0.086) but a significant subgroup difference was seen only for eosinophils, where concentrations were significantly lower in the PZ than in the control group among children with baseline plasma zinc concentrations below the overall median (524 ± 44 compared with 600 ± 41 cells/μL, P = 0.012). Conclusions: Zinc supplementation of rural Laotian children had no effect on cytokines or T-cell concentrations, although zinc supplementation affected lymphocyte and eosinophil concentrations. These cell subsets may be useful as indicators of response to zinc supplementation. This trial was registered at clinicaltrials.gov as NCT02428647.